(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study deals with the geometrical optimization and energies of three structures of carbon nanoribbon using the B3LYP-DFT hybrid functional. 6-31G basis sets was employed to study the effect of the ribbons length on the energies and electronic properties of the structures. The results showed that the hybrid functional used is suitable for calculations the geometrical parameters of the structures. So, the energy gap was increased with increasing the length of the ribbon due to the change of both the HOMO and LUMO energies of the carbon nanoribbons. The shortest the ribbon the higher electronic softness and the more reactive it is as compared to the long ribbon